INTERDISCIPLINARY PROGRAM TO IDENTIFY RISK FACTORS FOR THE MOST COMMON INFECTIOUS DISEASES IN THE POPULATION OF RUSSIA THROUGH SCREENING LABORATORY TESTS - D. N. Stolyarova (LLC "Diagnostics and Vaccines", 2015)
The article presents the information of start Interdisciplinary program to identify risk factors for the most common infectious diseases in the population ofRussiathrough screening laboratory tests with a view to timely detection and prevention of infectious diseases in children inRussia.